Risk of prolapse and urinary complications in adult spina bifida patients with neurogenic acontractile detrusor using clean intermittent catheterization versus Valsalva voiding. Issue 1 (12th October 2018) - El Akri, Mehdi; Brochard, Charlène; Hascoet, Juliette; Jezequel, Magali; Alimi, Quentin; Khene, Zine‐eddine; Richard, Claire; Bonan, Isabelle; Kerdraon, Jacques; Gamé, Xavier; Manunta, Andrea; Siproudhis, Laurent; et al.
Abstract : Aims: To assess the relative risks of pelvic organ prolapse (POP) and urinary complications in adult spina bifida patients with neurogenic acontractile detrusor voiding with Valsalva versus those using clean‐intermittent catheterization (CIC). Methods: We conducted a retrospective analysis including all spina bifida patients with neurogenic acontractile detrusor with a minimum follow‐up of 12 months. Patients were then divided in two groups according to their bladder management: voiding with Valsalva versus CIC. The primary endpoint was any de novo or worsened rectal and/or pelvic organ prolapse (POP) diagnosed during follow‐up. The secondary outcome was urinary complications defined as febrile urinary tract infections (UTI) and/or urolithiasis and/or renal failure. Results: Fifty‐five patients (50.9% were males) met the inclusion/exclusion criteria: 28 voiding with Valsalva and 27 performing CIC. At baseline, the rates of vaginal prolapse (44.4% vs 50%; P = 0.99), and rectal prolapse/intussusception (25.9% vs 21.4%; P = 0.76) were similar in both groups. After a median follow‐up of 80.6 and 65.6 months, respectively ( P = 0.29), the rate of de novo or worsened rectal prolapse/intussusception was higher in the Valsalva voiding group than in the CIC group (32.1% vs 3.7%; P = 0.01). De novo or worsened vaginal prolapses were also more common in the Valsalva voiding group, but it did not reach statistical significance (33.3% vs 11.1%; P = 0.29). Conclusions: Valsalva voiding might be harmful in adult spina bifida patients with neurogenic acontractile detrusor as it may increase the risk of rectal prolapse/intussusception. Overall, the prevalence of POP and rectal prolapse was high in both groups.